2015
DOI: 10.1007/s10592-015-0736-y
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure and genetic diversity of the threatened White Mountain arctic butterfly (Oeneis melissa semidea)

Abstract: The White Mountain arctic butterfly [WMA;Oeneis melissa semidea (Say)] is endemic to the alpine zone of Mts. Washington and Jefferson, New Hampshire, USA, and because of its small and declining population size, it is considered threatened. White Mountain arctic adults occur only within four alpine meadows, and it has been suggested that dispersal, and hence gene flow, may be restricted among these meadow subpopulations. Furthermore, although the WMA likely is biennial (i.e., requires 2 years for development) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 86 publications
0
6
2
Order By: Relevance
“…For example, across 17 species reviewed in the study by Gradish et al (2015), 12 show a considerably higher proportion of polymorphic loci than we observed in the Behr's hairstreak (values ranging from 0.35 to 1.00, compared to a range of 0.19-0.34 in the Behr's hairstreak) and only one species shows a lower value (≤0.17). Among the 14 of those species for which expected heterozygosity (H E ) estimates were also available, nine show higher values than the Behr's hairstreak (values ranging from 0.10 to 0.46 versus a range of 0.07-0.11 in the Behr's hairstreak) and only two species showed lower values (≤0.06) (Gradish et al, 2015). Interestingly, the Behr's hairstreak shows very similar levels of diversity to endangered populations of the Mormon metalmark from southern British Columbia, which are also at their northern range periphery and for which the proportion of polymorphic loci ranges from 0.17 to 0.23 and H E ranges from 0.07 to 0.09 (Crawford et al, 2011).…”
Section: Discussionmentioning
confidence: 49%
“…For example, across 17 species reviewed in the study by Gradish et al (2015), 12 show a considerably higher proportion of polymorphic loci than we observed in the Behr's hairstreak (values ranging from 0.35 to 1.00, compared to a range of 0.19-0.34 in the Behr's hairstreak) and only one species shows a lower value (≤0.17). Among the 14 of those species for which expected heterozygosity (H E ) estimates were also available, nine show higher values than the Behr's hairstreak (values ranging from 0.10 to 0.46 versus a range of 0.07-0.11 in the Behr's hairstreak) and only two species showed lower values (≤0.06) (Gradish et al, 2015). Interestingly, the Behr's hairstreak shows very similar levels of diversity to endangered populations of the Mormon metalmark from southern British Columbia, which are also at their northern range periphery and for which the proportion of polymorphic loci ranges from 0.17 to 0.23 and H E ranges from 0.07 to 0.09 (Crawford et al, 2011).…”
Section: Discussionmentioning
confidence: 49%
“…Some organisms have a two‐year life cycle, with individuals that breed in alternate years being reproductively separated from each other. The White Mountain arctic butterfly ( Oeneis melissa semidea ), a threatened butterfly endemic to four sedge meadows in New Hampshire, USA, provides an example (Gradish, Keyghobadi, & Otis, ). While no genetic differentiation was found between meadows, sympatric allochronic cohorts exhibit moderate differentiation (Gradish et al., ).…”
Section: Role Of Allochrony In Speciationmentioning
confidence: 99%
“…The White Mountain arctic butterfly ( Oeneis melissa semidea ), a threatened butterfly endemic to four sedge meadows in New Hampshire, USA, provides an example (Gradish, Keyghobadi, & Otis, ). While no genetic differentiation was found between meadows, sympatric allochronic cohorts exhibit moderate differentiation (Gradish et al., ). Pink salmon ( O. gorbuscha ) provide another example of populations breeding in alternate years, in addition to seasonal allochrony (above); yearly cohorts are genetically differentiated, and genetic differentiation is stronger between cohorts than among populations breeding within the same year in different rivers (Aspinwall, ).…”
Section: Role Of Allochrony In Speciationmentioning
confidence: 99%
“…In addition, microsatellites are inherently difficult to use in butterflies, partially due to the high frequency of null alleles [49]. Therefore, ISSR genetic markers have been widely applied in studies on butterfly population genetic [15][16][17]43,48,[50][51][52][53][54][55][56][57].…”
Section: Issr-pcr Amplificationmentioning
confidence: 99%